STRATEGI KOMUNIKASI STASIUN RADIO DALAM MENGHADAPI KONVERGENSI MEDIA - Pupu Jamilah (Jurnal Ilmu Komunikasi PROGRESSIO, 2021)
AbstractThis study aims to determine the communication strategy of Radio Tjandra FM Cianjur in facing media convergence. The subjects of this study consisted of 6 employees who knew the strategy and implementation of media convergence on Tjandra FM Cianjur radio, either as policymakers or policy implementers in the field. The basis of the theory used is New Media by Pierre Levy. This research uses qualitative research methods with a case study approach. Data collection activities used were interviews, observation, and documentation.The results of this study found that to adapt to current technological advances, namely the internet. (1) Tjandra FM Radio converges media by combines conventional media with internet media. That is, not only doing on air but also marketing content through social media, such as Facebook, Twitter, Instagram, websites, and radio streaming applications. (2) Tjandra FM Radio branding audiences for promotion and image building. The strategy is carried out by not only broadcasting on air but also off-air using OB Van (On Board Van), as well as being an event organizer at an event. Keywords: Communication strategies, qualitative, media convergence.